Silent in the sanctuary : a Lady Julia Grey mystery - Raybourn, Deanna (Don Mills, Ont. : MIRA Books, 2009)
Lady Julia returns home from a sojurn in Italy and joins family and friends at her father's estate in Sussex. The homecoming celebrations turn ghastly when one of the guests is found murdered and Julia's cousin confesses to the crime. Certain that her cousin is innocent, Julia sets out to discover the truth with the help of Nicholas Brisbane.
Sequel to: Silent in the grave.
Keywords: Grey, Julia (Fictitious character) -- Fiction; Widows -- England -- Fiction; Women detectives -- England -- Fiction; Private investigators -- England -- Fiction; Upper class -- England -- History -- 19th century -- Fiction; England -- Social life and customs -- 19th century -- Fiction; Historical fiction; Mystery fiction; Historical mystery fiction